(untitled) (Revista Ciência Agronômica, 2018)
The present work was performed by applying the principal component analysis, in order to compare the water needs of banana, mango, grape, sugarcane, maize and beans crops in different regions of the São Francisco river basin, aiming to identify the climate elements that most influence the reference evapotranspiration (ET0 ) in the locations of Pirapora-MG, Jaíba-MG, Barreiras-BA and Petrolina-PE. In addition, the locations with more similarities, according to the evaluated parameters, were verified by applying cluster analysis, and the equivalence relations between the studied crops were determined by integrating the parameters related to the climatic elements and the characteristics of crops and soils. Based on the principal components analysis, it was observed that the most significant climate elements for ET0 estimation were different for each place. The model with two components explained 90%, 88%, 95% and 97% of the total variance, respectively for the locations of Pirapora, Jaíba, Barreiras and Petrolina. Because it is in a semi-arid climate region, Petrolina showed high crop water needs, a behavior proven with the cluster analysis. The equivalence relations allowed comparing the water needs for the studied crops, providing, in general terms, a parameter comparison between the crops, and specifying which one will be more adequate depending on the water availability in the São Francisco basin.